Gambaran tingkat kecemasan orang tua dengan Anak Berkebutuhan Khusus (ABK) dan penanganannya di UPTD PSBK Provinsi Sulawesi Tenggara - Annisa, Rizki; Opod, Hendri; Sinolungan, Jehosua Samratson Victor (UNIVERSITAS SAM RATULANGI, 2024)
According to 2021 data, the number of Indonesia children with autism has increased to 2.4 million. Government established the UPTD Autism Service Centre (PLA) which handle early age autism therapy, which later changed to UPTD for Handling Children with Special Needs (PSBK) which broaden to early age children with special needs. However, the long therapy period (6 months to 5 years), limited therapist staff, and limited equipment creating a long queue therapy service, has caused anxiety among parents of Children with Special Needs (ABK). This was a descriptive quantitative method research with univariate data analysis techniques, with univariable: